BUILDING SUPPORT NETWORKS: THE ROLE OF THE FAMILY IN THE CARE OF PEOPLE LIVING WITH HIV - Costa Silva, Lays; Corrêa Villela Neto, Antônio; Gregório da Silva, Fabiana; Araújo de Carvalho, Raquel (Health and Society, 2024)
HIV/AIDS is more than a physical illness, affecting not only the body, but also the social, economic, mental life and quality of life of people who live with it. Over time, these people have shown a growing interest in not only prolonging life with treatment, but also in living well, adapting their health condition naturally to everyday life. The family plays a fundamental role in this health and illness process. Often, it is to the family that the individual turns for support when coping with the disease. Therefore, this study aimed to examine how family relationships influence people living with HIV/AIDS. To do this, we searched for information in databases such as SciELO and VHL, using keywords such as “Family”, “HIV” and “Quality of Life”, combined with the “AND” operator. After analyzing a series of criteria, we selected 10 relevant articles for our review. Thus, it was possible to realize that, although the family plays an important role in quality of life, it is just one of the many variables that influence the lives of people with HIV/AIDS. This influence can be positive or negative, depending on the nature of the relationship between the person and their family after the diagnosis.